2019
DOI: 10.1002/jso.25367
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intramural and extramural vascular invasion on stage II‐III colon cancer outcomes

Abstract: Background and Objectives: Vascular invasion, in particular extramural venous invasion (EMVI), is a pathologic characteristic that has been extensively studied in rectal cancer but rarely in colon cancer. This study aims to evaluate its prognostic role in stage II-III colon cancer. Methods: All stage II-III colon cancer patients who underwent surgery between 2004–2015 were reviewed. We divided the study group into patients without invasion, with intramural invasion only (IMVI), EMVI only, and both IMVI/EMVI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 21 publications
(20 reference statements)
3
50
0
1
Order By: Relevance
“…However, overemphasis on LNM in the colon cancer TNM staging system is controversial. Many studies have reported the prognostic impact of high-risk features beyond LNM [11][12][13][14][15][16][17][18][19][20][21][22][23]. One study showed the relationship between the number of high-risk features and prognosis, demonstrating that 5-year OS rate was less than 20% in patients with stage II colon cancer with four or more high-risk features [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, overemphasis on LNM in the colon cancer TNM staging system is controversial. Many studies have reported the prognostic impact of high-risk features beyond LNM [11][12][13][14][15][16][17][18][19][20][21][22][23]. One study showed the relationship between the number of high-risk features and prognosis, demonstrating that 5-year OS rate was less than 20% in patients with stage II colon cancer with four or more high-risk features [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinicopathological significance of EMVI in CRC has already been studied, EMVI based on tumor location and evaluation methods is not available. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Arterial blood is supplied from the outer layer to the inner layer of the gastrointestinal tract and comes out as venous blood. If a tumor cell invades into the vessel, regional, and distant metastases can be induced through the venous flow.…”
Section: Discussionmentioning
confidence: 99%
“…The following data were collected from the full texts of eligible studies: the first author's name, study location, information of tumor, year of publication, number of patients analyzed, evaluation method of venous invasion, the rates of EMVI, and the data for survival rate. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] We did not define a minimal number of patients to be included in a study. The estimated hazard ratio (HR) and its standard error using given parameters, which were the HR point estimate, log-rank statistic or its P value, O-E statistic (difference between numbers of observed and expected events), or its variance, were aggregated.…”
Section: Data Extractionmentioning
confidence: 99%
“…Specifically, vascular invasion was defined as extramural venous invasion, as this has been shown to carry a significantly worse prognosis than small-vessel and intramural venous invasion. 34 The slides for all ≥pN1 cases were reviewed to assess nodal and tumour deposit status within the initial and subsequent lymph node dissections. pN1c cases were analysed separately because, unlike for nodal metastases, tumour deposit staging is binary and not influenced by the number of tumour deposits.…”
Section: A T a C O L L E C T I O N A N D A N A L Y S I Smentioning
confidence: 99%